A review of the application and development of nanospheres for cancer treatment. - Jacildo, Patricia Gayle
With the invasive and damaging nature of the current conventional approaches to treating cancer, nanotechnology provides a promising potential for cancer treatment. Thus, this study presents a comprehensive overview of recent advancements in utilizing nanospheres for cancer treatment. Specifically, the fabrication methods, surface functionalization, and cancer treatment applications were examined and cross-analyzed across 69 studies. A heatmap analysis revealed a concentration of studies in Asian countries, while none were found specifically from the Philippines. Results show that carbon, gold, and silica nanospheres are typically fabricated using hydrothermal-carbonization, citrate reduction, and sol-gel methods, respectively. Notably, the synthesis process is influenced by three main factors: precursor amount, reaction time, and reaction temperature. Specifically, carbon nanospheres exhibit a strong and positive correlation between these factors and the resulting diameter. Silica nanospheres demonstrate exceptional versatility in facilitating the conjugation of numerous ligands, while gold nanospheres showcase remarkable multi-modal imaging capabilities. Furthermore, additional surface modification shows an enhancement in the specific targeting abilities of the nanospheres for ligands composed of vitamins, chemicals, ions, proteins, carbohydrates, and nucleic acid moieties, or cell membranes. Folic acid emerges as the most common surface modification route for targeting a variety of cancer cells. However, a lack of studies on gold nanosphere sensors is a gap that needs to be addressed. Additionally, efforts should be made to encourage research in the field of nanotechnology for cancer treatment in the Philippines, as it is currently underrepresented in the literature. Overall, the findings underscore the immense potential of carbon, gold, and silica nanospheres in the realm of cancer treatment, particularly for drug delivery, bioimaging, and cancer detection. These insights contribute to advancing nanotechnology-driven strategies for more effective and targeted cancer therapies, warranting further research to optimize their clinical applications and enhance treatment outcomes.